Very High Frequency Ultrasonographic Features of Trichofolliculoma: An Observational Study - Dong B; Xie B; Xia HS; Wang SB; Zhang YT (Journal of Multidisciplinary Healthcare)
Bin Dong,1 Bo Xie,2 Hong-sheng Xia,1 Shi-bo Wang,2 Yu-Ting Zhang2 1Department of Ultrasound, Hangzhou Third People’s Hospital, Hangzhou Third Hospital Affiliated to Zhejiang Chinese Medical University, Hangzhou, People’s Republic of China; 2Department of Dermatology, Hangzhou Third People’s Hospital, Hangzhou Third Hospital Affiliated to Zhejiang Chinese Medical University, Hangzhou, People’s Republic of ChinaCorrespondence: Yu-Ting Zhang, Department of Dermatology, Hangzhou Third People’s Hospital, Hangzhou Third Hospital Affiliated to Zhejiang Chinese Medical University, West Lake Road 38, Hangzhou, 310009, People’s Republic of China, Email zhangyuting0916@sina.comBackground: Trichofolliculoma (TF) is a rare condition, and its imaging features have been inadequately studied, leading to frequent misdiagnoses in clinical practice.Objective: The aim of our study was to investigate the very high frequency (VHF) ultrasound characteristics of TF, identify features that could assist in the differential diagnosis of TF versus other benign and malignant lesions.Methods: We collected clinical data from 24 patients with histologically confirmed TF between February 2019 and June 2024. We retrospectively analyzed the VHF ultrasound image characteristics of the lesions, including their location, skin layers involved, size, shape, margin, boundary, internal echo characteristics, and blood flow patterns.Results: The VHF ultrasound image features of the 24 TF cases showed that the lesions were located in the epidermis, dermis, and subcutaneous tissue in 8 cases, in the dermis and subcutaneous tissue in 2 cases, and in the deep dermis and subcutaneous tissue in 14 cases. The maximum diameter was approximately 23.3× 8.7 mm. The lesions were mostly regular in shape (75%), with predominantly inhomogeneous low echo (95.8%). Most lesions contained cystic echoes (70.8%), some had short linear strong echoes within (66.6%), and partial posterior echo enhancement was observed in some lesions (41.6%). Half (50%) of the lesions showed peripheral blood flow signals. The consistency analysis of the VHF ultrasound image features showed Kappa values greater than 0.7, indicating good agreement.Conclusion: The VHF ultrasound images of TF exhibit characteristic features. Specifically, the identification of the lesion’s location, the involved skin layers, internal echo features, and blood flow patterns offers novel insights that enhance diagnostic accuracy and possesses significant auxiliary value in clinical diagnosis and treatment. This study contributes unique findings to the existing literature, further elucidating the VHF ultrasound characteristics of TF and underscoring its potential in improving clinical practice.Keywords: very high frequency ultrasonic, diagnosis, trichofolliculoma